Epstein-Barr virus negativity among individuals older than 60 years is associated with HLA-C and HLA-Bw4 variants and tonsillectomy - Durovic, Bojana; Gasser, Olivier; Gubser, Patrick; Sigle, Jörg; Hirsch, Hans H; Stern, Martin; Buser, Andreas; Hess, Christoph (Journal of virology, 2013)
Epstein-Barr virus (EBV) infects ≈ 95% of the adult population. The factors that confer protection in the remaining ≈ 5% remain unknown. In an exploratory study, we assessed immunogenetic factors and tonsillectomy in a cohort of 17 EBV-negative and 39 EBV-positive healthy individuals aged >60 years. Analyses of HLA genotypes revealed an association between EBV negativity and the presence of HLA-C-35T/T and/or HLA-Bw4 alleles. In addition, EBV-negative donors presented with a history of tonsillectomy more often than EBV-positive donors.